Asymmetric synthesis of natural products - Ari M.P.Koskinen (Wiley, 2012)
"Natural product synthesis has played a key role in the development of many synthetic methods and will continue to do so in the future. Many recent advances in such diverse fields as immunology, cellular biology and materials science have been achieved through the synthetic chemist's ability to construct often very complicated structures in one enantiomeric form.Asymmetric Synthesis of Natural Products, 2nd Edition introduces students to this rapidly growing field of organic chemistry. The initial chapters present the foundations of asymmetric synthesis, including the theory and applications of individual asymmetric reactions. This is followed by chapters on each of the major individual classes of natural products; their structures, biosynthesis and interrelationships as well as examples of asymmetric syntheses and the practical value of these compounds. Natural product classes covered include carbohydrates, amino acids, peptides, proteins, nucleosides, nucleotides, nucleic acids, polyketides, isoprenoids, shikamic acid derivatives and alkaloids.For this second edition the text has been thoroughly updated and expanded, and includes new discussions and examples covering atom and redox economies, practical aspects and environmental awareness. Organocatalysis has emerged completely in the last ten years, and has been fully integrated into this new edition.Asymmetric Synthesis of Natural Products, 2nd Edition will find a place on the bookshelves of advanced undergraduates and postgraduates working in natural products chemistry, organic synthesis, medicinal chemistry and drug discovery. It is also useful for practising researchers who want to refresh their knowledge of the field"--